The influence of theory planned behavior factors on intention to whistleblowing academic fraud in accounting students - Kusumojati, Putri Pramestiwi; Arief, Meta; Widyaningsih, Aristanti (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to investigate the impact of Theory Planned Behaviour Factors on the Intention to Whistleblowing Academic Fraud in Accounting Students. The research method used is SLR (Systematic Literature Review), which involves the identification, analysis, evaluation, and interpretation of previous studies in the 2013-2023 time span, found through the Google Scholar database. From the results of the study, it is concluded that there are three main factors in Theory Planned Behavior, namely Attitude towards behavior, Subjective Norms, and perceived behavioral control, which significantly affect the intention to whistleblowing academic fraud in Accounting Students.